A - 1/2 * 1/3xy =
b - x/3 *(-9)=
c - 2/3t : (-3) =
d - 1/7z: (-5/14)=
e - 3(2x+3) =
f - -2(7-2y)=
g - (2a+b)*(-5)=
h - 1/2 (4a+1) =
i - -2/3(6y-9)=
j - -0,2(-b - 1) =
k - -(4x+3-1/2y)=
l - -5(-3a+b-0,7) =
m - -(-1/2t-2-6)=
n - (2x+8):(-2) =
o - (a-10):5=
p - ( 9x-7y-3) : 3 =
r - (-4z-2t):1/2 =
s - (4w-2+3u):(-1 i 1/3 )=
t - (0,6x+10y-1) : (-0,2) =
o - 2x - (-4-3x) =
p - 10-2(t+1) =
r - -3(2y+1/3) + 4y =
s - -6(1-0,5u)+3u/2=
t - 2(3w-1)- w+2/2 =
u - 3(a-2b)-5(b-2a) =







przepraszam ze tak mało punktów ale tylko tyle mam pilne na dziś błagam

1

Odpowiedzi

2010-03-01T23:39:30+01:00
a)1/2 * 1/3xy =1/6xy
b)x/3 *(-9)=-3x
c)2/3t : (-3) =-2/9t
d) 1/7z: (-5/14)=-2/5z
e) 3(2x+3) =6x+9
f)-2(7-2y)=-14+4y
g)(2a+b)*(-5)=-10a-5b
h)1/2 (4a+1) =2a+1/2
i) -2/3(6y-9)=-4y+6
j)-0,2(-b - 1) =0,2b+0,2
k) -(4x+3-1/2y)=-4x-3+1/2y
l)-5(-3a+b-0,7) =15a-5b+3,5
m) -(-1/2t-2-6)=1/2t+2+6=1/2t+8
n)(2x+8):(-2) =-x-4
o)(a-10):5=1/5a-2
p)( 9x-7y-3) : 3 =3x-7/3y-1
r)(-4z-2t):1/2 =-8z-4t
s) (4w-2+3u):(-1 i 1/3 )=(4w-2+3u):(-4/3)=-3w+3/2-9/4u=3w+1 i 1/2-2 i1/4u
t)(0,6x+10y-1) : (-0,2) =-3x-50y+5
o) 2x - (-4-3x) =2x+4+3x=5x+4
p)10-2(t+1) =10-2t-2=8-2t
r)-3(2y+1/3) + 4y =-6y-1+4y=-2y-1
s) -6(1-0,5u)+3u/2=-6+3u+3/2u=-6+4 i1/2u
t)2(3w-1)- w+2/2 =6w-2-w+1=5w-1
u)3(a-2b)-5(b-2a) =3a-6b-5b+10a=13a-11b